IMPLEMENTASI KANTIN KEJUJURAN DALAM MENINGKATKAN KEJUJURAN DAN TANGGUNG JAWAB SISWA - Farah Amalia Idris; Muhammad Munif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article aims to describe and analyze in depth the implementation process of the honesty canteen in enhancing students’ honesty and sense of responsibility. This study employs a qualitative research method with a case study approach. The research setting is MTs. Hikmatul Ulum Sumberkedawung Leces Probolinggo, conducted from February to April 2025. Data collection techniques include interviews, observations, and documentation. The data analysis in this study adopts the Miles and Huberman model, consisting of data reduction, data display, and conclusion drawing. The results show that the implementation process of the honesty canteen in fostering honesty and responsibility among students at MTs. Hikmatul Ulum Sumber kedawung Leces Probolinggo is carried out through the provision of an Unattended Canteen (Self-Service), Independent Purchase Transactions, and the Omplong Payment System.